Challenges of Digital Transformation on Good Governance for Improving Public Services Quality - Nanda Wahyu Indah Kirana; Nurkholish Majid (Nusantara Science and Technology Proceedings, 2021)
Public institutions provide services continually to strive for quality improvement through good governance. Along with the transformation of the digital era, Good Governance is synchronized with digital-based services in terms of Digital Governance. This study's purpose is to examine how digital transformation in public service can be improved the quality of Good Governance. The digital transformation successfully can be reached through the collaboration between user experiences and senior digital experts. However, Digital Governance encounter several challenges including a lack of relationship between institutional managers with stakeholders as users and the risk of protecting data sources that are prone to leakage. Therefore, good governance still needs to be improved continuously so that it can provide benefits to the wider community. One benefit of implementing good governance of government institutions is the formation of a smart city that results in the convenience and welfare of the community.